Case Report: PCI of the left coronary artery after salvage operation in a comatose patient with an acute type A aortic dissection - Jan Bidovec; Jan Bidovec; Petar Risteski; Petar Risteski; Barbara E. Stähli; Omer Dzemali; Omer Dzemali; Michael Hofmann; Michael Hofmann; Julia Stehli (Frontiers in Cardiovascular Medicine, 2025)
A 74-year-old female was found hemiplegic in a public restroom. After arrival in our stroke unit, a computed tomography (CT) was performed, and she was diagnosed with bilateral carotid artery and right vertebral artery occlusion due to an acute type A aortic dissection. The patient deteriorated quickly to a GCS of 3 and was brought to the operating room, where a salvage replacement of the ascending aorta and the proximal aortic arch was performed with unilateral antegrade cerebral perfusion. Three days later, a significant decrease in left ventricular function and increase in cardiac biomarkers were observed. Coronary CT displayed residual dissection of the aortic root, extending into the left main coronary artery. The patient underwent an intravascular ultrasound-guided stenting of the left main, resulting in total recovery of heart function. She was extubated on the fourth postoperative day, with no residual neurological impairment. This case report advocates for the proper management of patients with ATAAD with severe neurological impairment, emphasizing the importance of a robust multidisciplinary approach in their care.